Use of electron microscopy in examination of faeces and rectal and jejunal biopsy specimens. Issue 4 (April 1991) - Connolly, G M; Ellis, D S; Williams, J E; Tovey, G; Gazzard, B G
Abstract : The stools and rectal biopsy specimens of 44 patients with AIDS and diarrhoea were examined by culture, light microscopy, and electron microscopy. In 13 patients examination of rectal biopsy material and faecal samples showed no pathogen, but in two of these, microsporidiosis was found by electron microscopical examination of jejunal biopsy specimens. This organism was also identified electron microscopically in one of the further five jejunal biopsy samples taken from patients with a known cause of diarrhoea. Blastocystis hominis infection was identified electron microscopically in six patients, all of whom had cryptosporidiosis additionally seen by light microscopy. Four of these six patients remained well for long periods, with only moderate diarrhoea, and follow up showed no evidence of blastocystis infection. In only four of 11 patients found to have cryptosporidium in their stools at light microscopy were organisms found at electron microscopy. Viral inclusions were only identified at electron microscopy in one of 10 patients with an opportunistic viral infection seen at light microscopy (cytomegalovirus n = 7, herpes simplex virus n = 3). No additional viral pathogens were detected in either stools or rectal biopsy material by electron microscopy. It is concluded that routine electron microscopic examination of stool samples or rectal biopsy material taken from patients with AIDS and diarrhoea is unnecessary and does not increase the yield of potential pathogens compared with standard microbiological techniques and histology.